Analisis ketuntasan hasil belajar biologi Siswa Kelas Xi Semester 1 SMA Negeri Kampar Tahun Pelajaran 2006/2007 - Yusuf, Yustini; Tambunan, Erika (Jurnal Pilar Sains, 2008)
The aim of the research is to know the result of the students´lerning of senior high school Negeri Kampar,Kampar district which has running on the Curriaelum Based on Competence (KBK). This research was doneat Kampar district from September to December 2006. The population of this research are all the students atthe XI degrees of the govermant school senior high school Negeri Kampar, academic year 2006/2007, whilethe sample of the research are the students at the XI degrees of Senior High School Negeri 2 Air Tiris, SeniorHigh School Negeri 2 Bangkinang and Senior High School i Kampar. This is a descriptive research,parameter of measurement is the level of the final of individual learning and clasicall which is include of theaspect of cognitif, psicomotor and affective. The result of this analysis of the final of biology learning of thestudents at the XI degrees of the first semester in Senior High School Negeri Kampar academic year2006/2007, the highest of cognitife ability of the clasicall final based on the national standard is Senior HighSchool Negeri 2 Air Tiris XI degress science mayor (60%), the highest level for the psicomotor ability basedon the national standard is Senior High School Negeri 1 Kampar Xi degrees science mayor (64.28%) and thehighest leave] for the clasicall final of the affective ability based on the national standard is Senior HighSchool Negeri I Kampar XI degrees science mayor (92.85%).Keyword: final Result, Biology, Curriaelum Based on Competence (KBK).